The internal determinants of bank profitability and stability: An insight from banking sector of Pakistan - Ali, M.; Puah, Chin Hong (Emerald Publishing Limited, 2019)
The purpose of this study is to examine the internal determinants of bank profitability and stability in Pakistan banking sector. Because of specific research objectives, this study excludes the external factors of profitability and stability to find the role of bank internal determinants in achieving high performance.